Analysis of the Effect of Fraud Pentagon Model in Predicting the Occurrence of Fraudulent Financial Statements - Farrah Geubrina Rezeki (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This study aims to determine the effect of the Fraud Pentagon Model on predicting the occurrence of Fraudulent Financial Statements in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Pentagon Fraud Model is a development of Fraud Triangle Theory and Fraud Diamond, including opportunity, pressure, competence, rationalization, and arrogance. The sample consisted of 83 manufacturing companies listed on the Indonesia Stock Exchange from 2016-to 2018, selected using the purposive sampling method. The data analysis method used is multiple regression with SPSS version 25.0. The results of this study indicate that pressure and arrogance influence the prediction of Fraudulent Financial Statements. While rationalization, opportunity, and competence have no effect in predicting the occurrence of Fraudulent Financial Statements.